Presence of massive open online courses for accelerating One Health basic training in Indonesia - Putra, Luqman Suyanto; Sutisna, Anan; Herlina, Herlina (Universitas Negeri Yogyakarta, 2024)
New Emerging diseases and re-emerging diseases that are major threats to public health continue to have serious social, political, and economic impacts. In coordination with other sectors, the weak Indonesian health resilience system makes cross-sector involvement with the One Health approach (human, animal, environmental) very important. One Health Training is an effort to raise awareness about the importance of collaboration, coordination, and communication with various sectors regarding human, animal, and environmental health. This study aims to provide an overview of the existence of MOOC learning models for One Health Basic Training. The study uses qualitative research methods with a scoping review approach. This study reinforces the study of MOOCs' learning model for Health Training. This research is limited specifically to articles related to World Health Training that have implemented the MOOC learning model. The findings of this study provide insight into the various factors that need to be considered and the relevance of applying the learning model of MOOCs to One Health Basic Training.